Pengaruh Kualitas Pelayanan dan Citra Merek Terhadap Keputusan Penggunaan Jasa (Studi kasus pada pada pelanggan AHASS 1013 Cahaya Abadi Kaligarang Kota Semarang) - Nina Karina; Sudharto Prawata Hadi (Universitas Diponegoro, 2018)
AHASS 1013 Cahaya Abadi is an authorized Honda Service Center providing repair and maintenance servicing, and sparepart selling. The research problem is the amount of customer’s at AHASS 1013 Cahaya Abadi is fluctuatve that tend to decline. It indicates the low of service use decision. AHASS 1013 Cahaya Abadi needs to take attention about the factors affecting it in order to create strategies in competing with other AHASS workshop outlets. The purpose of this study is to identify the influence of service quality and brand image for service use decision. The type of this research is explanatory research. The sample used are 97 respondents of AHASS 1013 Cahaya Abadi’s customer’s. The sampling techniques is accidental sampling. The data collection techniques are questionnaire and literature review. Data analysis techniques are using classic assumption, correlation, simple linear regression, multiple linier regression, t and F test with IBM SPSS (Statistical Product dan Service Solutions) program version 23.0. The results of this study showed that the service quality has an effect on service use decision with a correlation coefficient about 0,651 and determination coefficient about 42.4%, brand image itself has an effect on service use decision with a correlation coefficient about 0,702 and determination coefficient about 4,39%. The conclusion of this study is, that service quality and brand image influence to the service use decision. The recommendations proposed follows. It is necessary to evaluate its service quality and to strengthen the brand image of product.